New Tetramic Acids Comprising of Decalin and Pyridones From Chaetomium olivaceum SD-80A With Antimicrobial Activity - Wang, Xinzhu; Zhao, Liya; Liu, Chao; Qi, Jun; Zhao, Peipei; Liu, Zhaoming; Li, Chunlei; Hu, Yingying; Yin, Xin; Liu, Xin; Liao, Zhixin; Zhang, Lixin; et al. (Frontiers in Microbiology, 2020)
Cycloaddition reactions such as intramolecular Diels–Alder (IMDA) are extremely important in constructing multicyclic scaffolds with diverse bioactivities. Using MycB as a biomarker, three new polyketides – Chaetolivacines A (1), B (3), and C (4) – with one known compound Myceliothermophin E (2) comprising of decalin and 4-hydroxy-2-pyridones were obtained from the culture of Chaetomium olivaceum SD-80A under the guidance of gene mining. The structures of these compounds were established using detailed 1D, 2D NMR, and high-resolution electron spray ionization mass spectroscopy (HRESIMS) analysis. The relative and absolute configurations of the compounds 1, 3, and 4 were elucidated by NOESY and ECD. The biosynthesis pathways of these compounds were proposed, which involves in three key genes ChaA [polyketide synthase-non-ribosomal peptide synthetases (PKS-NRPS)], ChaB, and ChaC. Compounds 1–4 were tested for their antimicrobial activities, and compounds 2 and 3 showed moderate bioactivity against Staphylococcus aureus (SA) and methicillin-resistant S. aureus (MRSA) with MIC values of 15.8 and 27.1 μM. The results showed that configuration of C-21 in 3 and 4 is important for anti-SA and anti-MRSA activities. This study reveals the significant potential of the genus Chaetomium in producing new PKS-NRPS, therefore increasing the speed in the mining for new sources of antimicrobial agents.